Taxes, Profit Shifting, and the Real Activities of MNEs: Evidence from Corporate Tax Notches - Jaqueline Hansen; Valeria Merlo; Georg Wamser (Center for Economic Studies and ifo Institute (CESifo), 2023)
We exploit exogenous variation in tax notches created by controlled foreign corporation (CFC) rules to better understand the profit-shifting behavior of multinational enterprises (MNEs) and its consequences for real activity. Using new data on CFC rules and information on direct parent-affiliate ownership links, our identification approach allows us to estimate an unbiased profit-shifting semi-elasticity of about 0.22. Removing incentives to shift profits to particular low-tax locations leads to profit relocation to 'next-best' low-tax countries, allowing firms to circumvent domestic taxation. We do not find any significant effects on parent shareholders, neither in terms of repatriated profit nor in terms of their real economic activity. Other entities within the MNE, where profits get relocated to, see a significant increase in various measures of real activity.
Keywords: F23; H25; 330; corporate taxation; profit shifting anti-tax-avoidance rules; multinational enterprise; firm organization